Expressing Chinese-ness: An Alternative Imagery among Young Chinese Indonesians - Ignatia Dyahapsari; Irfan Nugraha (Antropologi Indonesia, 2020)
After the 1998 reformation, Chinese Indonesians become more open in expressing their identity in the public sphere in everyday life. However, a pivotal moment for Chinese Indonesians began with Ahok’s engagement with the political life, even though he then tripped in a political ploy that finally turned off Chinese collective hope for equality. On the one hand, anti-Chinese sentiment was reproduced as a tool for political segregation. On the other hand, young Chinese Indonesians are actively expressing their identity and political preferences through social media. We argue that the expressions shared publicly by young Chinese Indonesians might portray a different reflection of identity which is closely related to the political changes of the contemporary Indonesian society. Through their public expressions, new imagery of Chinese Indonesian was created as an alternative to the state-forced imagery on their Chinese-ness. This paper elaborates on how the current imagery produced and reproduced by young Chinese Indonesians through new mediums of social media in response to the continuous political conflict in their daily life.